Gully erosion, land use and topographical thresholds during the last 60 years in a small rangeland catchment in SW Spain (Land Degradation & Development, 2009)
Gully erosion plays an important role in degradation processes of Mediterranean environments. In this paper aerial orthophotographs were used for (i) analysing the evolution of a valley bottom gully and its relation with land use and vegetation cover, (ii) exploring the role of land use and vegetation cover on the coefficients of the equation S = aA−b (where S is slope at the headcut and A is drainage area), which is based on the topographical threshold concept and is commonly used to predict gully initiation. The study was carried out in a small catchment (99·5 ha) located in the southwest of the Iberian Peninsula. Gullies and headcuts were mapped together with land use and vegetation cover using aerial photographs for the years 1945, 1956, 1989, 1998, 2002 and 2006, which had to be digitized and orthorectified in advance. The results showed an increase of the area affected by gullying from 695 m2 in 1945–1009 m2 in 2006, reaching a maximum of 1560 m2 in 1956. Gullying was closely related with land use, especially with the amount of cultivated areas within the catchment and also with grazing intensity. No clear relationship was found between the evolution of the gullied area and rainfall amounts. Finally, the values of the exponent b obtained for different headcuts and different dates (close to 0·4) were similar to those proposed by other authors for gully erosion caused by Hortonian overland flow in semiarid environments. Copyright © 2009 John Wiley & Sons, Ltd.